Association between blood pressure and dementia in older adults: a cross-sectional study from China - Yi, Tingting; Su, Zhou; Wang, Jiyang; Gan, Jinghuan; Wu, Hao; Shi, Zhihong; Sun, Zhen; Liu, Shuai; Ji, Yong (Frontiers in Aging Neuroscience, 2024)
The association between blood pressure (BP) and dementia in older adults remains unclear, prompting this study to investigate the relationship between various BP indicators and dementia in this population.A cross-sectional survey was conducted in 2019, including 3599 participants aged 65 years or older. The basic demographic characteristics of participants were collected. BP measurements and neuropsychological assessments were performed. From the systolic BP (SBP) and diastolic BP (DBP) values, mean arterial pressure (MAP), pulse pressure (PP) and blood pressure index (BPI) were calculated. Generalized additive models and logistic regression models were used to analyze the association between BP indicators and dementia.Results: Generalized additive models identified a U-shaped relationship between DBP and dementia, which was more significant in males and people 70 years of age and older. The optimal DBP associated with the lowest dementia risk was 85 mmHg.Logistic regression models revealed that compared to the DBP subgroup (80-89 mmHg), participants in the DBP < 80 mmHg subgroup and the DBP ≥100 mmHg subgroup had OR for dementia of 1.611 (95% CI: 1. 252-2.073, P ＜ 0.001) and 1.423 (95% CI: 0.999-2.028, P = 0.050), respectively. A significant association was observed between BPI and dementia (OR:1.746 95% CI: 1.142-2.668, P = 0.010).In older adults, we found a U-shaped relationship between DBP and dementia, and a linear relationship between BPI and dementia. These results underscore the importance of considering DBP and BPI in BP management strategies for older adults to potentially prevent or delay dementia onset.